Beyond the BICs : identifying the ‘emerging middle powers’ and understanding their role in global poverty reduction /: identifying the ‘emerging middle powers’ and understanding their role in global poverty reduction. (December 2010) - Scott, James, 1977-; Vom Hau, Matthias; Hulme, David
No abstract available